The expression of comparison ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Comparison, often known as comparing, is the process of discovering the features of two or more items are similar, distinct, and to what extent by first identifying the pertinent, comparable characteristics of each. When features differ, the differences can be compared to decide which thing is most appropriate for a certain use.